PROFESSIONAL TRAINING OF BORDER GUARDS IN PROFILING PERSONS - Madžuls, Juris (Border Security and Management, 2023)
The author of the paper explores the content of the qualification improvement course “Profiling, Interviewing, Identification” implemented in the State Border Guard College of the Republic of Latvia, the questionnaires given to the course participants in order to develop the guidelines for more effective training of border guards in the field of profiling and provides his point of view, taking into account training on profiling delivered in national and international context and level. The paper is aimed to identify the possibilities of improving the border guards’ professional background in performing profiling in line with the current socio-economic, political and migration trends in Europe and in the world. The research was done in the State Border Guard College of the Republic of Latvia and several Central Asia region countries. For this purpose analysis and evaluation of documents, scientific, pedagogical and psychological literature was performed and suggestions for the improvement of border guard training system in the field of profiling were compiled. The author concludes that the current SBGC lecturers` level of proficiency allows to develop and implement any length and content qualification improvement course in the field of profiling. The author recommends to develop a micro-learning approach, namely by creating a variety of short video training materials. Development of profiling methodological instructions at the central level of the State Border Guard would lead to the increase of profiler (border guard) activities efficiency in performing service duties and would allow to operate with profiling related terms, procedures and activities.